2024
DOI: 10.1002/adom.202301909
|View full text |Cite
|
Sign up to set email alerts
|

Ribbontail Stingray Skin Employs a Core–Shell Photonic Glass Ultrastructure to Make Blue Structural Color

Venkata A. Surapaneni,
Michael J. Blumer,
Kian Tadayon
et al.

Abstract: Structural blue colors are common in animals, with the tissue nanostructures and material systems that produce them—especially bright blues—typically based on highly ordered nano‐architectures. In this study, we describe an unusually bright and angle‐independent structural blue from the skin of ribbontail stingray, arising from a more disordered array of scattering elements with a previously undescribed core–shell ultrastructure, involving nano‐vesicles enclosing guanine nano‐platelets. We show that this skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 87 publications
0
0
0
Order By: Relevance
“…In contrast, we have recently shown that the blue color (reflectance peaks ∼447–452 nm) of the ribbontail stingray ( T. lymma ; Figure 1A ) is due to a novel type of iridophore that occurs in the epidermis and in exceptionally high density in the dermis, equipped with a stable colloidal system of crystal-containing vesicles (referred to as iridosomes in the present study) that coherently scatter incident light, while associated melanophores absorb the longer incident wavelengths ( Surapaneni et al, 2024 ). Surapaneni et al (2024) is the first study to describe structural color formation in elasmobranchs, using a combination of optical, histological and modeling methods to explain the basis for the non-iridescent blue of the ribbontail ray.…”
Section: Introductionsupporting
confidence: 43%
See 4 more Smart Citations
“…In contrast, we have recently shown that the blue color (reflectance peaks ∼447–452 nm) of the ribbontail stingray ( T. lymma ; Figure 1A ) is due to a novel type of iridophore that occurs in the epidermis and in exceptionally high density in the dermis, equipped with a stable colloidal system of crystal-containing vesicles (referred to as iridosomes in the present study) that coherently scatter incident light, while associated melanophores absorb the longer incident wavelengths ( Surapaneni et al, 2024 ). Surapaneni et al (2024) is the first study to describe structural color formation in elasmobranchs, using a combination of optical, histological and modeling methods to explain the basis for the non-iridescent blue of the ribbontail ray.…”
Section: Introductionsupporting
confidence: 43%
“…Specimens of the blue-spotted ribbontail ray T. lymma were from the same individuals used in Surapaneni et al (2024) , collected opportunistically from commercial fisheries operating off Singapore (Pulan Ubin–Changi area), Indonesia (Jakarta), and Kenya (Eastern Indian Ocean) between May 2017 and June 2022, following the sampling protocol by Mollen (2019) . Specimens in this study included two females, one adult of ∼26.0 cm DW (disc width) and 72.5 cm TL (total length) and one juvenile of ∼14.9 cm DW and 35.7 cm TL.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations